2021
DOI: 10.1111/1365-2664.13827
|View full text |Cite
|
Sign up to set email alerts
|

Experimental evidence that novel land management interventions inspired by history enhance biodiversity

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 64 publications
0
4
0
Order By: Relevance
“…Similar harvest patterns are being advocated in systems of ecology forestry that mimic natural disturbance regimes in temperate European forests, such as windfall, naturally occurring pests and diseases or disturbances associated with fauna species. Studies show positive results of restoring historical management or novel approaches inspired by history on the recruitment of shade‐intolerant species and on the biodiversity related to sun‐exposed habitat patches (Douda et al., 2017; Hawkes et al., 2021). From a pollinator point of view, forest management systems that benefit the herb layer vegetation such as traditional coppice systems, shelterwood or gap cutting are preferred to single tree selection systems.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar harvest patterns are being advocated in systems of ecology forestry that mimic natural disturbance regimes in temperate European forests, such as windfall, naturally occurring pests and diseases or disturbances associated with fauna species. Studies show positive results of restoring historical management or novel approaches inspired by history on the recruitment of shade‐intolerant species and on the biodiversity related to sun‐exposed habitat patches (Douda et al., 2017; Hawkes et al., 2021). From a pollinator point of view, forest management systems that benefit the herb layer vegetation such as traditional coppice systems, shelterwood or gap cutting are preferred to single tree selection systems.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, the 'N time bomb' hypothesis states that due to global changes and herbivory, the desired or expected herb vegetation or composition after these shifts might not even prevail (Segar et al, 2022). Management Hawkes et al, 2021). From a pollinator point of view, forest management systems that benefit the herb layer vegetation such as traditional coppice systems, shelterwood or gap cutting are preferred to single tree selection systems.…”
Section: Change In Pnp Over Timementioning
confidence: 99%
“…Previous studies, conducted as an integral part of the same experiment, have demonstrated that disturbed‐grassland also benefits Woodlark Lullula arborea (Hawkes et al ., 2019 a ), Eurasian Curlew Numenius arquata (Zielonka et al ., 2019) and priority (rare, scarce or threatened) dry‐grassland invertebrates (Hawkes et al ., 2019 b , 2021). Similar interventions may benefit other disturbance associated grassland waders, such as North American breeding populations of Mountain Plovers Charadrius montanus (Augustine & Skagen, 2014) and Upland Sandpipers Bartramia longicauda (Sandercock et al ., 2015), or Sociable Lapwings Vanellus gregarius in Central Asia (Kamp et al ., 2009).…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, we assumed that "Targeted" conservation actions achieve high growth rates for single species, while "Landscape" actions achieve limited growth rates for multiple species. However, we acknowledge that this assumption is a simplification and that there can be high variability in the impact of targeted and landscape actions, for instance due to the types of actions implemented and the shared ecological requirements of species (Hawkes et al, 2019(Hawkes et al, , 2021. Therefore, for targeted species, we applied growth rates of 0%-30%reflecting a range in the success of the species-specific actions.…”
Section: Case-study Informed Target-achievability Pathwaysmentioning
confidence: 99%